Development of a Malawi Intensive care Mortality risk Evaluation (MIME) model, a prospective cohort study. (December 2018) - Prin, Meghan; Pan, Stephanie; Kadyaudzu, Clement; Li, Guohua; Charles, Anthony
Abstract: Introduction: Intensive care medicine can contribute to population health in low-income countries by reducing premature mortality related to surgery, trauma, obstetrical and other medical emergencies. Quality improvement is guided by risk stratification models, which are developed primarily within high-income settings. Models validated for use in low-income countries are needed. Methods: This prospective cohort study consisted of 261 patients admitted to the intensive care unit (ICU) of Kamuzu Central Hospital in Malawi, from September 2016 to March 2018. The primary outcome was in-hospital mortality. We performed univariable analyses on putative predictors and included those with a significance of 0.15 in the Malawi Intensive care Mortality risk Evaluation model (MIME). Model discrimination was evaluated using the area under the curve. Results: Males made up 37.9% of the study sample and the mean age was 34.4 years. A majority (73.9%) were admitted to the ICU after a recent surgical procedure, and 59% came directly from the operating theater. In-hospital mortality was 60.5%. The MIME based on age, sex, admitting service, systolic pressure, altered mental status, and fever during the ICU course had a fairly good discrimination, with an AUC of 0.70 (95% CI 0.63–0.76). Conclusions: The MIME has modest ability to predict in-hospital mortality in a Malawian ICU. Multicenter research is needed to validate the MIME and assess its clinical utility. Highlights: Models created within and for low-income countries (LICs) are critical to improving the quality of global surgery and treatments for non-communicable diseases. We used prospective data for Intensive Care Unit patients at a referral hospital in Malawi to develop an ICU mortality prediction model for use in Malawi and other LICs. The Malawi Intensive care Mortality Evaluation (MIME) model provides modest discrimination for ICU mortality in Malawi, but requires external validation in other LIC populations before broad application.